2021
DOI: 10.7554/elife.66551
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting wide-band neural activity using convolutional neural networks

Abstract: Rapid progress in technologies such as calcium imaging and electrophysiology has seen a dramatic increase in the size and extent of neural recordings. Even so, interpretation of this data requires considerable knowledge about the nature of the representation and often depends on manual operations. Decoding provides a means to infer the information content of such recordings but typically requires highly processed data and prior knowledge of the encoding scheme. Here, we developed a deep-learning framework able… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Further, the points where agents switch between different options may be able to predict where rats and humans would pause in the maze 72 . More broadly, new approaches to RL 109 and deep learning methods may provide new ways to examine navigation 40, 110 , as well as integrating our approach with biologically-inspired network models that seek to explain neural dynamics during navigation 111, 112 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the points where agents switch between different options may be able to predict where rats and humans would pause in the maze 72 . More broadly, new approaches to RL 109 and deep learning methods may provide new ways to examine navigation 40, 110 , as well as integrating our approach with biologically-inspired network models that seek to explain neural dynamics during navigation 111, 112 .…”
Section: Discussionmentioning
confidence: 99%
“…Balaguer et al, 2016). More broadly, new approaches to RL 106 and deep learning methods may provide new ways to examine navigation 40,107 , as well as integrating our approach with biologically-inspired network models that seek to explain neural dynamics during navigation 108,109 .…”
Section: How Might the Rl Agents Be Improved?mentioning
confidence: 99%
“…Furthermore, the points where agents switch between different options may be able to predict where rats and humans would pause in the maze. 73 More broadly, new approaches to RL 111 and deep learning methods may provide new ways to examine navigation 41,112 as well as integrating our approach with biologically inspired network models that seek to explain neural dynamics during navigation. 113,114 Exploring the neural substrates of a predictive map Recent neuroimaging in humans has shown that activity in hippocampal and connected regions tracks the modeled parameters from a SR. 63,64,66,68,78 Convergent evidence in rodents suggests that the place-cell activity in the dorsal cornu Ammonis 1 (CA1) of rodents may operate as a SR. 67,68,71,115,116 Our protocol would allow for evidence from both rodent and human data to be integrated within a single framework to consider how patterns in the data may interrelate across species and in relation to the parameters from RL-modeled agents.…”
Section: How Might the Rl Agents Be Improved?mentioning
confidence: 99%
“…MINE specifically supports an encoding view, inspecting which information is encoded by the neurons of interest. Artificial neural networks have however also been used from a decoding perspective, probing what in-formation can be gleaned about ongoing behavior from neural activity 51,52 . Here we restricted the question of information encoding to individual neurons.…”
Section: Discussionmentioning
confidence: 99%